The impact of ill-discipline on the performance of grade nine learners : a case of Nghonyama High School in Limpopo Province - Masingi, Tintswalo Maria (My University, 2017)
The purpose of this study was to investigate the impact of ill-discipline on the performance of Grade nine learners at Nghonyama High School. The acts of indiscipline among students, especially at the secondary level of education are universal challenge thatmany schools face all over the world. A quantitative descriptive research wasconducted to determine if there was a relationship between conduct and performance of such learners. Data collection was done through completion of questionnaires. Two groups participated in the study: the first group consisted of fifty Grade nine learners and the second group was composed of ten educators - four members of the School Management Team and six teachers. The study revealed that learners misbehave at school due to variety of reasons such as, peer pressure, overcrowding, lack of parental support, inability to do the work, poverty, lack of motivation to succeed, disrespect, moral decay, not being engaged in the formulation of rules, rules being not enforced, lack of parental care, unmonitored TV viewing, child-headed families, lack of effective disciplinary measures, poor perception of the aims and principles of schooling and poor home upbringing. The study further revealed that the most common types of illdiscipline in the area of study were vandalism, fighting, absenteeism, indecent dressing, substance abuse, bullying, stealing, smoking, and drinking alcohol. With ill-discipline academic performance is affected.The study equally revealed that the Department of Education is not doing enough to address the issue of infrastructure. For example, overcrowding is still a challenge. In other words, the school environment plays a role in promoting ill-discipline; if classes are overcrowded learners are forced to misbehave. The study recommends that teachers should be encouraged to refer cases of indiscipline to the School Management Team. Principals should also be encouraged to involve all stakeholders in the formulation of school rules. Parents must make sure thatschool rules are adhered to by all the learners, no matter whose child breaks the rule,and most importantly learners should be encouraged to cooperate well with their educators.
Thesis (M. Dev.) -- University of Limpopo, 2017.
Keywords: Ill-discipline; Academic performance; Grade nine learners; School discipline -- South Africa -- Limpopo; Classroom management -- South Africa -- Limpopo; High school students -- Attitudes